A metal-free aerobic oxidative bromination of anilines and aryl ketones with 2-methylpyridinium nitrate as a reusable ionic liquid. Issue 5 (May 2020) - Li, Ming-Fang; Wang, Jian; Ke, Yong-Xin; Pan, Song-Cheng; Yin, Hong; Du, Wenting; Li, Jing-Hua
An aerobic oxidative bromination of anilines and aryl ketones catalyzed by recyclable 2-methylpyridinium nitrate ionic liquid is achieved in water using hydrobromic acid as the bromine source and molecular oxygen as the oxidant. The catalytic system shows good efficiency and atom economy.